Combinatorial Mutagenesis and Selection to Understand and Improve Yeast Promoters. (6th June 2013) - Berg, Laila; Strand, Trine Aakvik; Valla, Svein; Brautaset, Trygve
Abstract : Microbial promoters are important targets both for understanding the global gene expression and developing genetic tools for heterologous expression of proteins and complex biosynthetic pathways. Previously, we have developed and used combinatorial mutagenesis methods to analyse and improve bacterial expression systems. Here, we present for the first time an analogous strategy for yeast. Our model promoter is the strong and inducible P A O X 1 promoter in methylotrophic Pichia pastoris . The Zeocin resistance gene was applied as a valuable reporter for mutant P A O X 1 promoter activity, and we used an episomal plasmid vector to ensure a constant reporter gene dosage in the yeast host cells. This novel design enabled direct selection for colonies of recombinant cells with altered Zeocin tolerance levels originating solely from randomly introduced point mutations in the P A O X 1 promoter DNA sequence. We demonstrate that this approach can be used to select for P A O X 1 promoter variants with abolished glucose repression in large mutant libraries. We also selected P A O X 1 promoter variants with elevated expression level under induced conditions. The properties of the selected P A O X 1 promoter variants were confirmed by expressing luciferase as an alternative reporter gene. The tools developed here should be useful for effective screening, characterization, and improvement of any yeast promoters.